Netflix et les mutations des pratiques de visionnage : entre rupture et continuité - Catherine Dessinges; Lucien Perticoz (Communiquer)
The main objective of this contribution is to identify “real” consumption practices for young audiences (18-25 years old) of audiovisual content on Netflix. Without limiting ourselves to series, we are also focusing our attention on a possible shift to other audiovisual content types offered by the platform to question the place of Netflix in the audiovisual and media cultures of this population. The methodology combines a quantitative survey (questionnaire that collected 2017 responses) and a qualitative approach (two focus groups and recording notebooks). The main results notably highlight a certain continuity between audiovisual practices on Netflix and those which existed before, to capture it.